A real‐world comparison of docetaxel versus abiraterone acetate for metastatic hormone‐sensitive prostate cancer. (10th August 2021) - Tsaur, Igor; Heidegger, Isabel; Bektic, Jasmin; Kafka, Mona; van den Bergh, Roderick C. N.; Hunting, Jarmo C. B.; Thomas, Anita; Brandt, Maximilian P.; Höfner, Thomas; Debedde, Eliott; Thibault, Constance; Ermacora, Paola; et al.
Abstract: Background: Docetaxel (D) or secondary hormonal therapy (SHT) each combined with androgen deprivation therapy (ADT) represent possible treatment options in males with metastasized hormone‐sensitive prostate cancer (mHSPC). Real‐world data comparing different protocols are lacking yet. Thus, our objective was to compare the efficacy and safety of abiraterone acetate (AA)+ADT versus D+ADT in mHSPC. Methods: In a retrospective multicenter analysis including males with mHSPC treated with either of the aforementioned protocols, overall survival (OS), progression‐free survival 1 (PFS1), and progression‐free survival 2 (PFS2) were assessed for both cohorts. Median time to event was tested by Kaplan–Meier method and log‐rank test. The Cox‐proportional hazards model was used for univariate and multivariate regression analyses. Results: Overall, 196 patients were included. The AA+ADT cohort had a longer PFS1 in the log‐rank testing (23 vs. 13 mos., p < 0.001), a longer PFS2 (48 vs. 33 mos., p = 0.006), and longer OS (80 vs. 61 mos., p = 0.040). In the multivariate analyses AA+ADT outperformed D+ADT in terms of PFS1 (HR = 0.34, 95% CI = 0.183–0.623; p = 0.001) and PFS2 (HR = 0.33 95% CI = 0.128–0.827; p = 0.018), respectively, while OS and toxicity rate were similar between both groups. Conclusions: AA+ADT is mainly associated with a similar efficacy and overall toxicity rate as D+ADT. Further prospective research is required for validation of the clinical value of the observed benefit of AA+ADT for progression‐free end‐points. Abstract : Abiratreone acetate outperforms docetaxel in terms of PFS and PFS2, while the impact on OS as well as the rate of side effects is similar between both groups in real‐life utilization. Prospective randomized trials of available agents in mHSPC are required to generate high‐level evidence to facilitate sensible drug selection